PATHOPHYSIOLOGY AND FUNCTIONS OF THE LIVER: A COMPREHENSIVE REVIEW - Turaev Umar Rahimovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The liver is one of the most vital organs in the human body, playing a central  role  in  metabolism,  detoxification,  and  synthesis  of  essential  proteins. Pathophysiological changes in the liver can result in a variety of disorders including cirrhosis, hepatitis, and hepatic failure. This article reviews the physiological roles of the liver and examines the key pathophysiological mechanisms underlying common liver diseases.